2002
DOI: 10.1073/pnas.162250899
|View full text |Cite
|
Sign up to set email alerts
|

The atomic structure of adeno-associated virus (AAV-2), a vector for human gene therapy

Abstract: The structure of the adeno-associated virus (AAV-2) has been determined to 3-Å resolution by x-ray crystallography. AAV is being developed as a vector for gene therapy to treat diseases including hemophilia, cancer, and cystic fibrosis. As in the distantly related autonomous parvoviruses, the capsid protein has a ␤-barrel fold, but long loops between the ␤-strands share little structural homology with other parvoviruses, leading to unique surface features. Most prominent are groups of threefold-related peaks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
643
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(657 citation statements)
references
References 61 publications
13
643
0
1
Order By: Relevance
“…39,40 Mutagenesis and crystal structure studies have identified the amino acids in the capsid of AAV2 responsible for HSPG binding. 41,42 Heparin has also been reported to compete for AAV3 binding to cells, implying that AAV2 and AAV3 may share HSPG as an attachment receptor. 18,43 Despite the fact that HSPG appears to be a major AAV2 attachment receptor for many cell types, other model systems have demonstrated considerable uptake of AAV2 in the absence of surface HSPG expression.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Mutagenesis and crystal structure studies have identified the amino acids in the capsid of AAV2 responsible for HSPG binding. 41,42 Heparin has also been reported to compete for AAV3 binding to cells, implying that AAV2 and AAV3 may share HSPG as an attachment receptor. 18,43 Despite the fact that HSPG appears to be a major AAV2 attachment receptor for many cell types, other model systems have demonstrated considerable uptake of AAV2 in the absence of surface HSPG expression.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
“…63 Studies focusing on AAV capsid structures have improved since the crystal structure of AAV2 was determined. Efforts to obtain capsid surface details for other AAV serotypes are accelerating 42,85 and have complemented genetic analyses of the AAV2 capsid that has revealed an enormous tolerance for large insertions such as GFP. 86 Such efforts to link sensitive fluorescent protein tags with AAV virions will enhance our capabilities to study AAV trafficking in real time.…”
Section: Future Directionsmentioning
confidence: 99%
“…The crystal structure of AAV2 has recently been published. 3 The structural determinants of AAV2 receptor binding to the heparan sulfate proteoglycan attachment receptor have also been delineated by various mutagenesis studies. 4,5 The differences in binding affinity to different receptors among the various serotypes are likely to be accounted for by differences within these structural determinants, since the key heparin-binding residues are different on nonheparin-binding serotypes.…”
Section: Structural Biology Of Aav Opens the Door To New Vector Designsmentioning
confidence: 99%
“…For example, these are highly ''constrained'' systems both structurally and functionally. Structurally, capsid proteins must maintain the ability to self-assemble into complex virion particles, placing inherent limitations on the engineering of individual subunits (Xie et al, 2002). Furthermore, viruses have evolved their genomes for shorter lengths, often taking advantages of alternative splicing and alternative reading frames to express multiple proteins from the same nucleic acid sequence (Fields et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this high ratio of biological function per nucleotide, when engineering one function, care must therefore be taken to avoid impairing others. Finally, viral properties whose molecular basis is distributed throughout the primary sequence of the capsid, such as virus-cell interactions (Chiorini et al, 1999;Opie et al, 2003) and antibody neutralization (Moskalenko et al, 2000;Wobus et al, 2000), will be extremely challenging to rationally re-design, even with the availability of AAV structures (Xie et al, 2002). Given these numerous complexities and constraints, library selection and directed evolution are particularly well suited for re-engineering viruses.…”
Section: Introductionmentioning
confidence: 99%